The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/f10090786
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the CL, DRIS and CND Methods in Assessing the Nutritional Status of Eucalyptus spp. Rooted Cuttings

Abstract: The efficiency of methods in adequately interpreting the nutritional status of Eucalyptus spp. rooted cuttings remains unknown. The aim was to evaluate the quality of diagnoses obtained using the critical level (CL), diagnosis and recommendation integrated system (DRIS) and compositional nutrient diagnosis (CND) methods to assess the nutritional status of Eucalyptus spp. rooted cuttings, based on two different yield indicators. The data were obtained from commercial nursery and calibration experiments, using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
14
0
3
Order By: Relevance
“…The leaf concentration in both clones growing in low K soil were below the K concentration recommended by Morais et al . (2019), regardless of the water conditions (Figure 4A,B). Under sufficient K, E. urophylla × camaldulensis had an increased leaf K concentration by water stress.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The leaf concentration in both clones growing in low K soil were below the K concentration recommended by Morais et al . (2019), regardless of the water conditions (Figure 4A,B). Under sufficient K, E. urophylla × camaldulensis had an increased leaf K concentration by water stress.…”
Section: Resultsmentioning
confidence: 90%
“…Overall, K concentration in leaves, stems, and roots was higher in plants grown with sufficient K than with low K in both clones (Figure 4). The leaf concentration in both clones growing in low K soil were below the K concentration recommended by Morais et al (2019), regardless of the water conditions (Figure 4A,B). Under sufficient K, E. urophylla × camaldulensis had an increased leaf K concentration by water stress.…”
Section: Drought-tolerant Eucalyptus Clones Increase K Concentration and Accumulation In Leaves And Stemmentioning
confidence: 84%
See 1 more Smart Citation
“…Also was observed a low RD to evaluate the CND method, adopting NRr = 0.00, even though this was the diagnostic method with the best performance to assess the nutritional P status in sugarcane [20]. To eucalyptus seedlings was found that the highest RD proportions were achieved by the most e cient method in the nutritional diagnosis, which varied according to the nutrient evaluated [24].…”
Section: Analysis Of Diagnosis Predictionmentioning
confidence: 94%
“…Plant tissue tests are thought to integrate the effects of growth factors on crop performance [ 10 ]. Regional tissue standards [ 11 ] have been developed to guide fertilization of Eucalyptus seedlings [ 8 , 12 , 13 ] and of trees more than 6 years of age [ 14 ]. No standards have been developed for trees of intermediate age.…”
Section: Introductionmentioning
confidence: 99%